Extrusão reativa da blenda PEAD/PP/PS com polímeros pós-consumo compatibilizada via reação de Friedel-Crats - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
An in situ compatibilization reaction is proposed for the post-consumer polymer blend of the polyolefins high-density polyethylene and polypropylene containing polystyrene, using the reactive extrusion process. In this approach, alkyl groups are grafted onto the aromatic rings of the polystyrene through the Friedel-Crafts chemical reaction. The synthesis of the compatibilizing agent generated during the polymer mixing process was proven in a previous work prior to this thesis. This work, therefore, presents a compatibilization route aimed at plastic recycling, applicable to post- consumer polymer fractions, specifically the polyethylene and polypropylene blend. The study thus presents two key issues regarding the problem: the feasibility of obtaining compatibilized polymer blends from polymers degraded during the continuous extrusion process, and the identification of critical points that require improvement to make the route suitable for post-consumer polymer fractions. For the first aspect, the proposed synthesis mechanism was applied to polymers with controlled degradation induced by the extrusion equipment itself. The characterizations conducted included the assessment of the degradation level, the morphological state resulting from the synthesis, and the mechanical behavior in tensile and impact tests, focusing on the effects associated with the presence of the compatibilizing agent. The resulting reactive blend demonstrated an improvement in interfacial interaction, evidenced by the increase in complex viscosity and storage modulus compared to the physical blend. The morphology revealed the emulsifying effect of the compatibilizing agent, as well as changes in the encapsulation pattern of the dispersed phase, indicating alterations in the thermodynamic affinities between the phases. Regarding the second aspect, reactive compatibilization was applied to real post-consumer polymers obtained from urban selective collection. The degradation level of these polymers was assessed through rheological analyses, correlating molecular weight with zero-shear viscosity and melt flow index. The resulting blend was investigated regarding the nature of the grafted groups through solubilization and differential scanning calorimetry. The morphological modifications resulting from the grafting were also explored. The presence of the compatibilizing agent was assessed through changes in rheological behavior and tensile mechanical properties, correlated with oscillatory mechanical analyses. Additionally, the thermal properties were examined through analytical and kinetic analysis. The rheological analysis of the reactive sets did not indicate the presence of compatibilizing agents. The comparison between the studied sets revealed greater interfacial interaction with the use of shorter-chain polystyrene. There was a preference for grafting onto the polystyrene chains by the secondary alkyl segments, as demonstrated by differential scanning calorimetry alongside the solubilization results. The morphology evidenced degradation resulting from the compatibilization reaction. The mechanical and thermal tests revealed the degradative effect of the compatibilization process, which resulted in mass loss of the polypropylene and polystyrene phases simultaneously with the compatibilization process.
Keywords: compatibilização; friedel-crafts; morfologia; reativa; reologia; compatibilization; friedel-crafts; morphology; reactive; rheology; Engenharia e Ciências de Materiais